TO THE ISSUE OF FINDING THE STOICHIOMETRIC COEFFICIENTS IN THE CHEMICAL REACTIONS - Aleksejeva, Jekaterina; Guseynov, Sharif (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
In the present paper, on the basis of the theory of inverse and ill-posed problems, an algorithm is proposed that allows to unambiguously determine the stoichiometric coefficients in the equations of chemical reactions of any type, including redox reactions and acid-base reactions, and, regardless of whether the constructed system of linear algebraic equations for the desired stoichiometric coefficients is underdetermined (i.e. there are fewer equations than unknowns) or overdetermined (i.e. there are more equations than unknowns). The proposed algorithm is a regularized algorithm (according to Tikhonov), which ensures that, in a computer implementation, possible computational errors will not make the comprised system of linear algebraic equations to be incapable of solving.